The Effect of Different Doses of Thyroxine Hormone Immersion on Egg Hatchabillity, Growth, and Survival Rate of Larvae (Colossomammacropomum) - Mursyd, Fadhillah; Alawi, Hamdan; Sukendi, Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe study was conducted on November 21, 2019, at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, Riau University, Pekanbaru. The purpose of this study was to determine the effect of the thyroxine hormone therouh the immersion of eggs on the hatchability, growth and survival of tambaqui fish larvae. The research method is an experimental design. The dosage of thyroxine hormone solution used was P1 (0 mg / L), P2 (0.05 mg / L), P3 (0.10 mg / L) and P4 (0.15 mg / L) for 24 hours. The results showed that the dose of the thyroxine hormone had a significant effect (P <0.05) on the fertilization rate (91.2%), hatching rate (92.05%), the increase in absolute length (1.60 cm),absolute weight (2.31gr), specific growth rate (24.8% / day) and survival rate (91.11%). The best dose of thyroxine hormone to increase fertilization rate is 0.15 mg / L while the best dose for egg hatchability, growth, specific growth rate and survival rate of freshwater pomfret fish is 0.10 mg / L. Water quality parameters during the study were temperature. 26-28ºC, pH 7,4-7,9; DO 5.4-5.9 mg / L.Keywords :Hatching rate, Thyroxine, Growth, ,larvae.